Work and family in Japanese society - Tsutsui, Junya (Springer briefs in population studies. Population studies of Japan, 2020)
This book analyzes Japan's fertility decline within the context of family life, gender roles, and employment practices. It argues that Japan has failed to build a dual-earner society, leaving women to choose between career and motherhood. The author highlights Japan's unique welfare model based on the male breadwinner and female homemaker system, where companies and families, rather than the state, provide welfare. This familialist orientation is shown to remain dominant and reinforced in policy, explaining the persistence of very low fertility in Japan.